Breast Cancer: global quality care optimizing care delivery with existing financial and personnel resources. (7th September 2020) - Verhoeven, Didier; Allemani, Claudia; Kaufman, Cary; Mansel, Robert; Siesling, Sabine; Anderson, Benjamin
Abstract : Our vision about breast cancer quality care within a global health framework was recently published by Oxford University Press. The aim of our work was to reflect on the potential to achieve a world-wide improvement in quality care, assessing value for money. The population-based survival estimates from the CONCORD programme and the Breast Health Global Initiative (BHGI) are valuable tools for this global effort. Because cancer care delivery is becoming unsustainable in many countries assessing healthcare value for the cost is becoming increasingly important. Recommendations are made for better global quality care for patients with breast cancer.